Rule: (Whosoever damages a thing to repel its harm isn‘t liable for Daman، but whosoever damages a thing to benefit from it is liable for Daman) – A Contemporary Applied Jurisprudential Study - AlRousan, Omar Fares Musallam; Bani Salamah, Mohammad Khalaf (Journal of Islamic Sciences, 2022)
This study aims to introduce the following rule of Daman (Guarantee): "Whosoever damages a thing to repel its harm isn`t liable for Daman، but whosoever damages a thing to benefit from it is liable for Daman." It achieves this through highlighting the meaning of this rule، evidence from Sharia، extent of application by jurists، and providing related examples.The study is based on the descriptive methodology utilizing the inductive tool in collecting the study material from its different sources and the analytical tool to highlight the findings.Both researchers recommend paying more attention to rules of Islamic jurisprudence and making them effective within the legislative framework. Accordingly، these rules should be included in various draft laws and annexed to the provisions of different laws to determine the ruling of Sharia on different cases encompassed by the law.
Keywords: Rules; Damaging; Guarantee